Hierarchical Porous Film with Layer-by-Layer Assembly of 2D Copper Nanosheets for Ultimate Electromagnetic Interference Shielding - Choi, Ho Kwang; Lee, Aram; Park, Mina; Lee, Dong Su; Bae, Sukang; Lee, Seoung-Ki; Lee, Sang Hyun; Lee, Takhee; Kim, Tae-Wook (AMER CHEMICAL SOC, 2021)
The emergence of technologies, such as 5G telecommunication, electric vehicles, and wearable electronics, has prompted demand for ultrahigh-performance and cost-effective shielding materials to protect against both the potentially harmful effects of electromagnetic interference (EMI) on human health and electronic device operation. Here, we report hierarchical porous Cu foils via an assembly of single-crystalline, nanometer-thick, and micrometer-long copper nanosheets and their use in EMI shielding. Layer-by-layer assembly of Cu nanosheets enabled the formation of a hierarchically structured porous Cu film with features such as multilayer stacking; two-dimensional networking; and a layered, sheetlike void architecture. The hierarchical-structured porous Cu foil exhibited outstanding EMI shielding performance compared to the same thickness of dense copper and other materials, exhibiting EMI shielding effectiveness (SE) values of 100 and 60.7 dB at thicknesses of 15 and 1.6 mu m, respectively. In addition, the EMI SE of the hierarchical porous Cu film was maintained up to 18 months under ambient conditions at room temperature and showed negligible changes after thermal annealing at 200 degrees C for 1 h. These findings suggest that Cu nanosheets and their layer-by-layer assembly are one of the promising EMI shielding technologies for practical electronic applications.